GAMBARAN FUNGSI KOGNITIF PADA PERAWAT GILIR DI RS CIPTO MANGUNKUSUMO - Hanartoaji A Pribadi, Sylvia F Lumempouw, Freddy Sitorus, Herqutanto (NEURONA, 2013)
INTRODUCTION ABOUT 75 HOSPITAL NURSES WORK IN SHIFT ONE OF NEGATIVE EFFECTS DUE TO LONG TERM SHIFT WORK IS COGNITIVE FUNCTION IMPAIRMENT MECHANISMS EXPLAINING THE COGNITIVE FUNCTION IMPAIRMENT ARE CHRONIC SLEEP DISORDER CIRCADIAN RHYTHM DESYNCHRONISATION AND WORK STRESS